In vitro inducible nitric oxide synthesis inhibitors from Alismatis Rhizoma - Kim, NY; Kang, TH; Pae, HO; Choi, BM; Chung, HT; Myung, SW; Song, YS; Sohn, DH; Kim, YC (PHARMACEUTICAL SOC JAPAN, 1999)
Bioassay-guided fractionation of an aqueous extract of Alismatis Rhizoma has furnished two inducible nitric oxide synthase (iNOS) inhibitory compounds, alismol (1) and alisol B monoacetate (2), together with an inactive triterpene, alisol C monoacetate (3). Compounds 1 and 2 inhibited nitric oxide (NO) synthesis in a dose-dependent manner in murine macrophage-like RAW 264.7 cells stimulated with interferon-gamma (IFN-gamma) plus lipopolysaccharide (LPS), The inhibitory effects of 1 and 2 on NO synthesis were partly due to suppression of iNOS mRNA expression as determined by Northern blotting.
Keywords: METHANOL EXTRACT